(2x)ysquared
-y + y equals 0.
For y - 2y - 3y equals 0, y equals 0.
3x3 - x2y + 12x - 4y = x2*(3x - y) + 4*(3x - y) = (x2 + 4)*(3x - y)
y - 3 = 0 y = 3
(2x)ysquared
x2y = k (constant) so 36 x 2 ie 72 is the constant. If x = 3 then y = 72/9 = 8
-y + y equals 0.
4 (apples) plus 3 (apples) = 7 (apples). 4 (cows) + 3 (cows) = 7 (cows) 4 (x2y) + 3 (x2y) = 7 (x2y)
For y - 2y - 3y equals 0, y equals 0.
3x3 - x2y + 12x - 4y = x2*(3x - y) + 4*(3x - y) = (x2 + 4)*(3x - y)
b = y - mx.
y= -2x
y - 3 = 0 y = 3
y=x+4
y = -6
(x4 + y4)/(x + y) = Quotient = x3 - x2y + xy2 - y3 Remainder = - 2y4/(x+y) So, x3 - x2y + xy2 - y3 - 2y4/(x+y)